ANALISIS TINGKAT KEPUASAN KONSUMEN PADA RESTORAN MIXUE MENGGUNAKAN LOGIKA FUZZY TSUKAMOTO (STUDI KASUS : RESTORAN MIXUE CABANG UNSIKA) - Aqmal Febrianto, Bagas; Kevin Zevanya Sarotona Mendrofa; Putra Ramadhan, Wanda; Rini Mayasari, (Journal of Computer Science and Technology (JCS-TECH), 2023)
By its very nature, restaurants depend on customer satisfaction in a competitive business world. In order to be the choice for customers, Mixue restaurant UNSIKA branch must be able to understand the extent to which customers are satisfied with their service and comfort. Understanding the level of customer satisfaction makes it key to meeting customer expectations, and achieving long-term success. This study aims to determine an effective way to determine the level of customer satisfaction using Tsukamoto fuzzy logic based on the results of customer satisfaction with services, facilities and comfort. By using the Fuzzy Tsukamoto method, it is hoped that this research can provide insight into preferences and expectations of mixue restoran services, as well as valuable input for mixue restaurant management in developing more effective strategies to increase customer satisfaction.